Analisis Sistem Informasi Akuntansi Penjualan Kredit Pada PT. SMS Surabaya - Riska Amelia; Diana Zuhroh; Wiratna Wiratna; Heri Toni Hendro; Tjandra Wasesa; Sutini Sutini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This line research aims to find out the lcredit sales laccounting information lsystems at LPT. lMS lSurabaya and ln ln to lnd out lhow lshould l lpt lpt lpt lpt lpt lpt lpt. lSurabaya SMS. The research method used is qualitative-descriptive, which is in nature to describe, describe, compare, some data and conditions as well as explain a situation in such a way that a conclusion can be drawn. The types of data used are qualitative data and quantitative data, with data sources namely primary data and secondary data which are collected using interview, observation, and documentation techniques. The results showed that the credit sales system at PT SMS did not function properly where the marketing department carried out credit sales transactions without a supervisor's account and direct billing to customers. Therefore, the application of a credit sales system according to theory is very necessary because there are 6 different functions in the credit sales system where each function is a controller or internal control.